VIDEO MICRO LEARNING: IMPLEMENTATIONS TPACK IN KINEMATICS LEARNING - Fahrunnisa, Nurmalia; Bakri, Fauzi; Nasbey, Hadi (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2024)
Abstract In 21st century learning, students are required to have 4C skills (critical thinking, creativity, collaboration, and communication). One way to practice 4C skills is with physics learning videos that implement TPACK. This study aims to produce learning videos that train 4C skills. The method used in this study is research and development using the Lee & Owens stages. The product feasibility of the results of this study was assessed by experts through a questionnaire instrument. The components of the questionnaire include the characteristics of learning videos, learning video components, learning models, TPACK implementation in learning, and the 4C learning stages, so that media experts, material experts, and learning experts say that physics learning videos are appropriate to use to train 4C skills in students. Keywords: 4C, Learning Videos, TPACK, Kinematics, Lee and Owens. Abstrak Memasuki pembelajaran abad 21 peserta didik dituntut untuk memiliki keterampilan 4C (critical thingking, creativity, collaboration and communication). Salah satu cara untuk melatih keterampilan 4C yaitu dengan video pembelajaran fisika yang mengimplementasikan TPACK. Penelitian ini bertujuan untuk menghasilkan video pembelajaran yang melatih keterampilan 4C. Metode yang digunakan dalam penelitian ini adalah Research and Development dengan tahapan Lee & Owens. Kelayakan produk hasil penelitian ini dinilai melalui instrumen kuesioner oleh para ahli. Komponen kuesioner meliputi karakteristik video pembelajaran, komponen video pembelajaran, model pembelajaran, implementasi TPACK dalam pembelajaran, dan tahapan pembelajaran 4C sehingga ahli media, ahli materi dan ahli pembelajaran menyatakan video pembelajaran fisika layak digunakan untuk melatihkan keterampilan 4C pada siswa. Kata-kata kunci: 4C, Video Pembelajaran, TPACK, Kinematika, Lee dan Owens.